Governance and Trusteeship Philosophy in the 2 G Saga - Kumar, Raj (Prabandhan: Indian Journal of Management, 2011)
The Indian ancient scriptures have cited the six faults(doshas) which are responsible for the generation of state of suffering, sorrow, misery, chaos, destruction of one's soul and eventually poor governance; namely Lust(kama); Anger(krodha); Greed(lobha); Delusion(moha); Arrogance(mada); and Envy or Jealousy(matsrya). 1 An Individual has to overcome all these obstacles to acquire the wisdom, which will support him in the discharge of his responsibility towards good governance. Similarly, keeping in view the healthy tradition of Indian philosophy, Gandhiji also refers to six "deadly enemies" which lead people astray and cause poor governance; lust, hatred, greed, error, pride and injustice 2. It is evident from the analysis of Indian scriptures that all these faults have been responsible for the dissolution of social life and a consequent revival of anarchy. Ravana, a powerful king, warrior and spiritual leader, caused his own downfall due to his extreme arrogance; Kansa and Hirnakashyup perished due to ignorance and hatred respectively. Duryodhana, another mighty king of Hastinapur ultimately died in the battle of Kurukshetra as a result of greed and envy. Along with him, all other silent spectators such as Bhishama, Daronacharya, Karna and other great warriors who were the part of adharma died ultimately. All these characters of Indian history failed to act upon the good advice of their well wishers. Therefore, our politicians, bureaucrats, army officers, judges, businessman and other powerful people should imbibe the lessons from the teaching of ancient scriptures that those individuals who will be part of adharma will sooner or later be exposed or perish. It is evident from the contemporary socio-political-economic environment that all these six deadly enemies of human soul, peace and prosperity have completely occupied the nature of human beings.